2020
DOI: 10.1002/berj.3674
|View full text |Cite
|
Sign up to set email alerts
|

Education and psychological distress in adolescence and mid‐life: Do private schools make a difference?

Abstract: This article extends the evidence base on childhood circumstances, education and psychological distress. We examine the link between childhood advantage and disadvantage, the type of school attended during adolescence and psychological distress at ages 16 and 42. The analysis uses a large, population‐based birth cohort study, the 1970 British Cohort Study (BCS70) (n = 17,198) using a structural equation modelling (SEM) approach. More advantaged young people were more likely to attend private schools, but we fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…It is important to note that the DSLs in the boarding schools were unconvinced by prevalent claims that the boarding school experience caused psychological harm to some children (Sullivan et al, 2021; Turner, 2019). They were particularly resistant to the accusation that boarding school environments constitute a form of child abuse, sometimes referred to as ‘normalised parental neglect’ or ‘privileged abandonment’ (Duffell & Basset, 2016; Schaverien, 2004; Schaverien, 2015), and that for some pupils boarding schools increase psychological distress (Sullivan et al, 2021; Turner, 2019). Conversely, they suggested that where children were exposed to abuse and neglect in their home environment or had emotionally absent parents, boarding school can be a place of safety and stability, and indeed may protect such children from neglectful parental behaviours.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that the DSLs in the boarding schools were unconvinced by prevalent claims that the boarding school experience caused psychological harm to some children (Sullivan et al, 2021; Turner, 2019). They were particularly resistant to the accusation that boarding school environments constitute a form of child abuse, sometimes referred to as ‘normalised parental neglect’ or ‘privileged abandonment’ (Duffell & Basset, 2016; Schaverien, 2004; Schaverien, 2015), and that for some pupils boarding schools increase psychological distress (Sullivan et al, 2021; Turner, 2019). Conversely, they suggested that where children were exposed to abuse and neglect in their home environment or had emotionally absent parents, boarding school can be a place of safety and stability, and indeed may protect such children from neglectful parental behaviours.…”
Section: Resultsmentioning
confidence: 99%
“…Emotional neglect is defined as carers who are unresponsive to a child's basic emotional needs, including failing to interact or give affection, and failing to nurture a child's self‐esteem and sense of identity (Howarth, 2007). Existing research highlights that children in affluent families may be subject to excessive pressures to achieve academically and to participate in a broad range of extracurricular activities, as well as experiencing isolation from their parents (Duffell & Basset, 2016; Schaverien, 2015; Sullivan et al, 2021), which puts them at increased risk of emotional and psychological distress, including anxiety disorders and depression, self‐harming behaviours, eating disorders and substance misuse problems (Luthar et al, 2013; Luthar & Becker, 2002; Luthar & Latendresse, 2006; Shermann, 2006). Further, two serious case reviews (SCRs) involving children from affluent backgrounds who have died (Carmi & Walker‐Hall, 2015) or suffered serious harm in their families (Brabbs, 2011) make evident that the safeguarding professionals were intimidated by the parents' social position, which significantly impacted how they interacted with the families and affected their ability to successfully intervene to secure the children's safety.…”
Section: Introductionmentioning
confidence: 99%
“…After controlling for SES and other socio-demographic and school characteristics, LS was higher in private or semi-private schools in six countries and lower in nine countries, suggesting that the wellbeing impact of attending private schools may differ by country. Studies in the UK have found that private schools offer no mental health and wellbeing advantages (Henderson et al, 2020 ; Sullivan et al, 2021 ), with evidence indicating that attending private schools is associated with more psychological distress at age 16 for females and predicts it at the age of 42 (Sullivan et al, 2021 ). Liu and Zhao ( 2016 ) found that Chinese youth attending private schools also reported lower LS, experiencing more racial discrimination than their public-school peers.…”
Section: Introductionmentioning
confidence: 99%